The 60s in Canada - Dessureault, Pierre; Hanna, Martha; Leclerc, Denise; Théberge, Pierre (Ottawa : National Gallery of Canada Ottawa, 2005)
Ashoona, Pitseolak ; Ayot, Pierre ; Barbeau, Marcel ; Baxter, Iain ; Beny, Roloff ; Bloore, Ronald ; Bourdeau, Robert ; Boyle, John ; Breeze, Claude ; Bronson, AA ; Burton, Dennis ; Bush, Jack ; Cameron, Eric ; Chambers, Jack ; Curnoe, Greg ; Curtin, Walter ; Dale, Jack ; Dallegret, François ; Delavalle, Jean-Marie ; Dickson, Jennifer ; Dille, Lutz ; Favro, Murray ; Fisher, Brian ; Flanders, John ; Gagné, Marc-André ; Gagnon, Charles ; Gaucher, Yves ; Gaudard, Pierre ; General Idea ; Gibson, Tom ; Grégoire, Normand ; Hayden, Michael ; Heath, Dave ; Herzog, Fred ; Hurtubise, Jacques ; Karkutt, Guenter ; Kennedy, Garry Neill ; Kiyooka, Roy ; Lambeth, Michel ; Lee-Nova, Gary ; Lemoyne, Serge ; Letendre, Rita ; Levine, Les ; Max, John ; McEwen, Jean ; McKay, Art ; Meredith, John ; Molinari, Guido ; Montpetit, Guy ; Morisset, Jean-Paul ; Morris, Michael ; Morrisseau, Norval ; Mousseau, Jean-Paul ; N.E. Thing Co. ; Pfeifer, Bodo ; Porter, Tim ; Rabinowitch, David ; Rabinowitch, Royden ; Ragee, Sakiassie ; Raginsky, Nina ; Rayner, Gordon ; Redinger, Walter ; Saint-Jean, Michel ; Saxe, Henry ; Semak, Michael ; Semchishen, Orest ; Shadbolt, Jack ; Snow, Michael ; Sullivan, Françoise ; Szilasi, Gabor ; Taconis, Kryn ; Tascona, Tony ; Tata, Sam ; Taylor, Jeremy ; Tousignant, Claude ; Tousignant, Serge ; Urquhart, Tony ; Vazan, Bill ; Whittome, Irène F. ; Wieland, Joyce
The Sixties : Photography in Question, The Sixties in Canada, Canadian Museum of Contemporary Photography, Ottawa, National Gallery of Canada, Ottawa, 2005-01-22. 2005-02-04, 2005-04-24. 2005-04-24
boek
Keywords: Canada